Environmental damage and the question of liability - Cora Wacker-Theodorakopoulos; Christoph Kreienbaum (Intereconomics, 1992)
The most effective way of preventing damage of any kind is to make the originator of the damage liable and to require him to rectify it. How can this principle, that works perfectly if a private good is damaged, be applied to the environment? Which are the advantages and limitations of a liability-based approach to environmental protection?
Keywords: 330; Environmental Policy